2019
DOI: 10.1097/md.0000000000015223
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection versus holmium laser enucleation of the prostate

Abstract: Objectives: The purpose of this study was to compare transurethral resection of the prostate (TURP) versus holmium laser enucleation of the prostate (HoLEP) in patients with benign prostatic hyperplasia (BPH) focusing on perioperative thrombin generation and fibrinolysis. Methods: Sixty-five BPH patients were prospectively randomly assigned to undergo TURP (n = 32) or HoLEP (n = 33). The prothrombin fragment (PF) 1+2, thrombin-antithrombin complex (TAT), tissue plasmino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In our study, focusing on the activation of coagulation, we demonstrated that F1+2 concentrations rose in response to surgery as previously described [37–39], but RIPC had no effect on F1+2 levels confirming recent findings in RIPC patients undergoing elective head and neck cancer surgery [17].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, focusing on the activation of coagulation, we demonstrated that F1+2 concentrations rose in response to surgery as previously described [37–39], but RIPC had no effect on F1+2 levels confirming recent findings in RIPC patients undergoing elective head and neck cancer surgery [17].…”
Section: Discussionsupporting
confidence: 91%
“…HoLEP is also associated with a shorter operative time, as reported by Song et al [40], Shah et al [41], Jhanwar et al [42], and Elshal et al [43]. However, there are findings of a longer operative time for HoLEP compared to Transurethral Resection of the Prostate (TURP), as reported by Sinha et al [44] and Bai et al [45], which aligns with the results of a recent systematic review on the same topic [31]. This suggests that TURP may be superior to HoLEP.…”
Section: Discussionmentioning
confidence: 84%
“…When it comes to HoLEP, it results in a shorter duration of hospital stay, as mentioned in studies by Jefferson et al [ 37 ], Elshal et al [ 43 ], Sinha et al [ 44 ], Bai et al [ 45 ], Prudhomme et al [ 46 ], and El-Hawy et al [ 48 ]. This is supported by a recent systematic review on the same topic [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…TAT, a complex created by the interaction of thrombin and antithrombin, is a reliable indicator of the body's thrombin levels. Elevated TAT indicates coagulation activation, which exists in cancer patients 31 . Yang et al 32 showed that patients with malignant tumors might use elevated plasma TAT levels to diagnose thrombosis because they signify an aberrant increase in coagulation and fibrinolytic activity.…”
Section: Discussionmentioning
confidence: 99%